2015
DOI: 10.1016/j.geoderma.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing soil aggregation and particulate organic matter responses to bioenergy crops across a topographic gradient

Abstract: Bioenergy crops have the potential to enhance soil carbon (C) pools fromincreased aggregation and the physical protection of organicmatter; however, our understanding of the variation in these processes over heterogeneous landscapes is limited. In particular, little is known about the relative importance of soil properties and root characteristics for the physical protection of particulate organic matter (POM). We studied short-term (3-year) changes in aggregation and POM-C pools under three cropping systems (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 96 publications
3
60
0
Order By: Relevance
“…Our own research confirms the stimulating effect of sewage sludge on soil enzymatic activity [51]. The increase in soil enzymatic activity can be explained primarily by the increase in the content of readily available carbon and nitrogen, and also by improvement of soil physicochemical properties [52][53]. On the other hand, research conducted by Yang et al [54] showed that Jerusalem artichoke roots reduce the negative effects of salinization, increasing diversity and the number of microorganisms, and thereby increasing soil enzymatic activity.…”
Section: Soil Enzymatic Activitysupporting
confidence: 83%
“…Our own research confirms the stimulating effect of sewage sludge on soil enzymatic activity [51]. The increase in soil enzymatic activity can be explained primarily by the increase in the content of readily available carbon and nitrogen, and also by improvement of soil physicochemical properties [52][53]. On the other hand, research conducted by Yang et al [54] showed that Jerusalem artichoke roots reduce the negative effects of salinization, increasing diversity and the number of microorganisms, and thereby increasing soil enzymatic activity.…”
Section: Soil Enzymatic Activitysupporting
confidence: 83%
“…Soil OC formation occurs via both a rapid dissolved organic matter–microbial path and a slower physical transfer path as litter fragments enter the soil (Cotrufo et al ., , ). A likely mechanism for SOC accumulation may be through incorporation of root fragments and microbial biomass C, necromass, and by‐products into aggregates in the absence of tillage (Six et al ., ; Ontl et al ., ; Tiemann & Grandy, ). Huang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, biofuel grasses cultivated with zero-tillage that had high productivity and roots with low lignin (i.e., high quality) and high decomposition rates accumulated the most SOC in this study. In temperate switchgrass systems, Ontl et al (2015) reported that crops that maximize root productivity would lead to the largest gains in protected soil C. On a longer time frame, as roots die and decompose with repeated ratooning, it seems likely that accessions with high root biomass, high proportion of root death upon ratoon, low total lignin concentration, and high proportion of readily degradable lignin monomers would accumulate the greatest amount of SOC.…”
Section: Functional Belowground C Dynamicsmentioning
confidence: 99%
“…In addition, we believe that root (mostly tiny roots) production in different soil depths is higher in semi‐arid rangeland compared with cultivated lands because of higher plant species number with different morphologies and structures. Indeed, SOM additions are governed by the volume of fibrous roots per unit of soil and their growth rate (Kadović et al, ; Yu & Jia, ; Ontl et al, ). In our study, the tiny dense shallow roots of poaceae such as poa bulbosa, P. pratensis, D. glomerata and Hordeum bulbosum may increase organic matter in the rangelands (Wang et al, ; Erfanzadeh et al, ; Peng et al, ).…”
Section: Discussionmentioning
confidence: 99%